Effect of supplementary parenteral nutrition on glucose and lipid metabolisms, risk of infection, and prognosis in critically ill patients with low body weight - Yang, Wen-Bin; Zhang, Wei; Zhang, Jian-Fang; Yang, Tu-Ying; Mo, Zhi-Feng (Digestive Medicine Research, 2019)
Background: While enteral nutrition (EN) is the preferred route of nutrition support, and total EN often fails to meet the nutritional needs of patients. A combination of multiple nutritional strategies can reach nutritional goals earlier and improve clinical outcomes. Methods: Totally 108 critically ill patients with a body mass index (BMI) of 0.05). After the treatment, the albumin level was significantly higher in SPN group than in EN group (P0.05). The actual calories and protein intakes in the SPN group were significantly higher than those in the control group (both P